Enterprise, business-process and information systems modeling : 17th international conference, BPMDS 2016, 21st international conference, EMMSAD 2016, held at CAiSE 2016, Ljubljana, Slovenia, June 13-14, 2016, proceedings /: 17th international conference, BPMDS 2016, 21st international conference, EMMSAD 2016, held at CAiSE 2016, Ljubljana, Slovenia, June 13-14, 2016, proceedings. (2016) - Unknown
No abstract available